Relation between motor perfomance and physical fitness level of schoolchildren - Capistrano R.* (2016)
Introduction: Children with poor motor performance, engage in less vigorous and organized activities, contributing to low scores in physical fitness assessments. However, there is no consensus in the literature about the association between variables. Objective: Evaluate the relationship between motor performance and physical fitness of students between 7 and 10 years old. Methods: Ninety-eight (98) students enrolled in a public school in Florianópolis, Santa Catarina State, Brazil, participated in this study. For motor evaluation, the Movement Assessment Battery for Children - Second Edition (MABC-2) was used; the assessment of physical fitness was performed using the guidelines of the Brazil Sport Project (PROESP-BR). Data were tabulated in the Statistical Package for Social Sciences (SPSS) for the descriptive statistical analysis (mean, standard deviation, frequency) and inferential analysis (Student's t-test, Mann-Whitney U test, and multiple linear regression test). The significance level was set at p < 0.05. Results: The values of the prevalence of motor difficulty and motor difficulty risk were 5.9% and 13.9%, respectively, and the value for without difficulty of movement was 80.2%. Differences were found for males in the agility tests and explosive strength of the lower limbs (p < 0.05), in which the boys with motor difficulty showed lower values. We noticed that abdominal strength, endurance, and agility significantly contributed to explain the variability in motor performance, which together showed a coefficient of determination (R2) of 0.13. Conclusion: Abdominal strength/endurance and agility contributed significantly in explaining the variability in motor performance. Thus, it is fundamental to encourage involvement in activities that contribute to the increase in motor repertoire reflecting physical fitness.